EFEKTIVITAS PROGRAM PMT PEMULIHAN TERHADAP KENAIKAN BERAT BADAN PADA BALITA STATUS GIZI BURUK DI KABUPATEN BANYUMAS - Anditia, Ersa; Suryandari, Artathi Eka; ., Walin (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
ABSTRACT: Based on preliminary surveys in 2012, the number of children underfive in Banyumas as many as 20 924 and as many as 1,458 (6.96%) children underfive were suffering malnutrition who were dispersed in 39 health centers, while as many as 119 were getting PMT (DKK Banyumas 2011 and 2012). Additional food was given once daily for 90 consecutive days. PMT program evaluation can be monitored from children underfive weight gain recorded every month. Determines the effectiveness of PMT recovery program to weight gain in children underfive malnutrition status in Banyumas. The study used retrospective analytic approach. The samples in this study are 54 underfive children were taken by random sampling. The research instrument used observation sheets and analysis tools using paired sample t test. Before giving PMT-Recovery program, toddler’s weight at least 5.5 kg while the maximum. Weight is 15.7 kg. After PMT-Recovery programs, children underfive’s minimum weight is 6.5 kg and a maximum is 16 kg. based on table 5, p value 0.000 and the hypothesis is accepted that PMT Recovery program is effective to children underfive’s weight gain in Banyumas regency. It’s mean that PMT Recovery program is effective to children underfive’s weight gain in Banyumas regency.Keywords : PMT-recovery, children underfive malnutrition, weight